338 Ultra-Early Cranioplasty Versus Conventional Cranioplasty: A Retrospective Review at an Academic Level 1 Trauma Center. (April 2023) - Chee, Keanu; Sethi, Akal; Kaakani, Alia; Beauchamp, Kathryn M.; Kang, Jennifer S.
Abstract : INTRODUCTION: Decompressive craniectomy (DC) is a common neurosurgical procedure for management of intracranial hypertension following traumatic brain injury. Traditionally, cranioplasty has been delayed for as long as three-to-six months following initial DC. Few studies have assessed the effect of 'ultra-early' cranioplasty on rates of postoperative complications following DC. METHODS: A retrospective review of cranioplasties performed at our institution between January 2016 and July 2020 was performed. Craniectomies performed at other institutions were excluded. Seventy-seven cranioplasties met inclusion criteria.Ultra-early cranioplasty was defined as cranioplasty performed within 30 days of craniectomy whereas conventional cranioplasty occurred after 30 days. Postoperative wound infection rates, rate of return to the operating room with or without bone flap removal, operative length, and rate of post-cranioplasty hydrocephalus were compared between the two groups. RESULTS: 39 and 38 patients were included in the ultra-early and conventional cranioplasty groups, respectively. The average number of days to cranioplasty in the ultra-early group was 17.7 ± 7.75 days compared to 95.7 ± 65.60 days in the conventional group. The mean GCS upon arrival to the ER was 7.28 ± 3.90 and 6.92 ± 4.14 for the ultra-early and conventional groups, respectively. The operative time was shorter in the ultra-early cohort that in the conventional cohort (ultra-early, 2.4 ± 0.71 hours; conventional, 3.0 ± 1.63 hours; p = 0.0336). The incidence of post-cranioplasty hydrocephalus was also lower in the ultra-early cohort (ultra-early, 10.3%; Conventional, 31.6%; p = 0.026). No statistically significant differences were observed regarding postoperative infection, return to the operating room, or bone flap removal. CONCLUSIONS: Our study shows that ultra-early cranioplasty can significantly reduce the rate of post-cranioplasty hydrocephalus, as well as operative time in comparison to conventional cranioplasty. However, the timing of cranioplasty following DC should remain a patient-centered consideration.